Governmental Research Support Programs and Private Entities in Slovakia - Zuzana Maliková; Matúš Kubák; Radovan Bačík; Miloš Fišar (Review of Economic Perspectives, 2015)
The paper analyses public subsidies aimed to enhance development and innovation in the Slovakian private sector. The paper reviews theoretical approaches of the necessity of public support to research and development activities in order to increase private investment in research and development. An overview of research and development support tools in Slovakia is presented. The analytical part of the work is oriented on a comparative analysis of two granting agencies in Slovakia [Agency for Research and Development (ARD) and Agency of Operational Program Research and Development (OPRD)]. Special attention is given to direct public financial support. Logit analysis showed a relationship between success of grant applicants and their characteristics. We find that the following have impact on success of the application: Age of the company, amount of the grant required, legal form of the company, and the agency to which the application for grant was submitted. Applicants with legal form Ltd. (limited liability company) have a higher chance of receiving grant than other legal forms. The highest chance of success has a request for a grant of up to 500.000 exteuro. According to the results of our analysis, the chance to obtain a grant decreases with each passing year.
Keywords: 330